Clinical Features of Acute Massive Pulmonary Embolism Complicated by Radiofrequency Ablation: An Observational Study. Issue 40 (October 2015) - Li, Yue-Chun; Lin, Jiafeng; Wu, Lianpin; Li, Jia; Chen, Peng; Guang, Xue-Qiang
Abstract : Abstract: Although pulmonary embolism (PE) complicated by radiofrequency catheter ablation (RFCA) is rare, it can be life-threatening. Our goal was to elucidate the clinical features of acute massive PE after RFCA. Of 2386 patients who underwent RFCA for supraventricular tachycardia or idiopathic ventricular arrhythmia, 4 patients (0.16%) whose cases were complicated by acute massive PE were examined. These 4 patients were female and middle-aged (range 43–52 years), and 2 of the 4 patients had iron-deficiency anemia and reactive thrombocytosis. Ablation in all patients was performed in the left heart via the right femoral arterial approach. All of the patients had a long-duration hemostasis procedure and bed rest following femoral arterial sheath removal after RFCA. All of the patients collapsed and lost consciousness during their ﬁrst attempt at walking after RFCA. The emergent electrocardiogram in 2 of the 4 patients revealed an S1 Q3 T3 pattern, 1 patient demonstrated new onset of right bundle-branch block (RBBB) and S1 Q3 pattern and Qr pattern in V1, and the remaining patient had negative T waves in leads V1, V2, and III. The emergent echocardiogram revealed right ventricular hypokinesis and pulmonary hypertension in the 4 patients with acute PE after ablation. Although all of the patients initially experienced sinus tachycardia when they recovered consciousness, 2 of the 4 patients suddenly developed intense bradycardia and lost consciousness again, and these patients finally died (50% fatality rate). All of the patients were identiﬁed by CT pulmonary angiography or pulmonary angiography. Our report suggests that although acute massive PE is highly rare, there is a real and fatal risk in patients who experienced acute massive PE after RFCA. Particular attention should be paid to the first ambulation after RFCA. Acute PE should be strongly suspected when sudden loss of consciousness occurs upon mobilization after RFCA. The new onset of S1 Q3 T3 pattern, RBBB or T wave inversion in the right precordial leads, and early detection of echocardiographic right ventricular dysfunction may be useful for making an early diagnosis of acute PE after RFCA. Early ambulation after left-sided RFCA might be helpful to prevent the formation of deep venous thrombosis and subsequent PE.